The Measurement of Acoustic Emission Signals from Stem of Maize Under Controlled Environment - Piyapong Sriwongras; Petr Dostál; Václav Trojan (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The present paper focuses on the acoustic emission (AE) measurement method for monitoring of plant transpiration system. AE signals from stem of investigated maize being under well watered condition throughout experiment is investigated with acoustic emission parameters evaluating unit of XEDO-AE system and environmental parameter sensor of XEDO-IO system (Dakel company, Czech Republic) for estimation of xylem cavitation and embolism occurring on stem of plant. After conducting experiment for 4 days, the experimental results indicated that great amounts of AE signals occurred during the daytime, whereas small amounts of AE signals occurred during the night and the variation of all environmental parameter values were associated with the change of AE values interestingly. To clarify the correlation between AE parameter and environmental parameters statistically, multi linear regression was used to describe this correlation. The statistical model showed that the environmental parameters affecting to the variation of an AE parameter value from strongest one to weakest one were air temperature, relative humidity, atmospheric pressure and light intensity at R2 = 68.7% and adjusted R2 = 68.4%. According to these experimental results, using AE method to monitor the investigated plant capable of illustrating the characterization of AE signals generated by plant being under well watered condition. Therefore, from this experiment, AE method could be used to be a tool for detecting whether plant is in well watered condition.